Description of the design and construction of a numerical control lathe (2005)
The implementation and results of a digital control system designed and built locally are presented. The mechanical system is described and the electronic and software systems, implemented to manufacture chess pieces from a drawing made in any graphic design software, are explained in detail. The basic algorithms and concepts of conversion to units of displacement of the actuators of the system are described. Likewise, the graphic interface that facilitates the interaction of the user (designer) with the CAD system is described.